2019
DOI: 10.3348/kjr.2018.0841
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Core Needle Biopsy Techniques for Intermediate or Low Suspicion Thyroid Nodules: Which Method is Effective for Diagnosis?

Abstract: ObjectiveTo retrospectively compare the diagnostic performances of two different ultrasound (US)-guided core needle biopsy (CNB) techniques for intermediate or low suspicion thyroid nodules.Materials and MethodsBetween August 2015 and December 2016, two different biopsy techniques were alternatively applied for 248 consecutive thyroid nodules, of which, 140 intermediate or low suspicion thyroid nodules were included in this study. In the first technique, two specimens included nodular tissue, nodular margin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…We proposed a flow chart for diagnosing FN close to FTC as to how patients should proceed safely and quickly (Figure ). A technique of US‐guided CNB for intermediate or low suspicion thyroid nodules has reported that obtaining two specimens with marginal targets is more effective for diagnosing neoplasm or malignancy . As an initial attempt, CNB is appropriate for nodules 2cm or larger.…”
Section: Discussionmentioning
confidence: 99%
“…We proposed a flow chart for diagnosing FN close to FTC as to how patients should proceed safely and quickly (Figure ). A technique of US‐guided CNB for intermediate or low suspicion thyroid nodules has reported that obtaining two specimens with marginal targets is more effective for diagnosing neoplasm or malignancy . As an initial attempt, CNB is appropriate for nodules 2cm or larger.…”
Section: Discussionmentioning
confidence: 99%
“…Core-needle biopsy (CNB) has emerged as a diagnostic tool for thyroid nodules based on recent advances in core biopsy devices (spring-activated single-or double-action needles) and the widespread use of highresolution ultrasonography (US) [8,9]. CNB has been reported to be an effective and safe diagnostic tool, as it allows clinicians to obtain a core tissue sample with potential information on architectural histological structures, thus enabling immunochemical staining [10][11][12][13]. Based on these advantages, many global guidelines have begun to recommend CNB as a diagnostic tool for thyroid nodules [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to simplify the nodule diagnosis, current thyroid guidelines (Thyroid Imaging Reporting And Data System (TIRADS)) advocate the use of ultrasonography (USG) as a preliminary test for all patients suspected of having thyroid nodule. 2,3 Clinical variables and ultrasound (US) findings as per the TIRADS guidelines are recommended as a primary criterion to assess the benign and malignant nature of a nodule. Based on these results, the clinician further advises an additional confirmatory testing (FNAB) or simple routine US follow-up.…”
Section: Introductionmentioning
confidence: 99%